Implementation Challenges of the Merdeka Curriculum in Elementary Schools: A CIPP-Based Systematic Literature Review (2023–2025) - Suci Lestari; Vina Iasha; Zulela MS (International Journal of Education and Learning Studies, 2026)
The Kurikulum Merdeka is an educational innovation designed to enhance learning flexibility by emphasizing essential competencies, literacy, numeracy, and the Pancasila Student Profile. However, its implementation at the elementary school level remains uneven and faces significant challenges. This study synthesizes findings from literature published between 2023 and 2025 using the CIPP (Context, Input, Process, Product) evaluation framework. The review identifies key issues, including disparities in teacher readiness, limited instructional resources, and inconsistent understanding of Merdeka Belajar principles across schools. Although several studies report improvements in literacy and numeracy outcomes, these gains are not evenly distributed, and notable differences persist between lower and upper grade classrooms. Principal leadership and teacher motivation emerged as critical enabling factors, while insufficient professional development, limited teaching modules, and inadequate technological infrastructure were major constraints. The study recommends strengthening teacher capacity through contextual, practice-oriented training, improving infrastructure, and implementing continuous supervision and mentoring to optimize Kurikulum Merdeka implementation in elementary education.